Penggunaan Pajum Pada Siswa Kelas II SD Negeri Merauke Materi Penjumlahan dengan Teknik Menyimpan - Wiwin Mariyanto; Yonarlianto Tembang; Martha Betaubun; Suryani Madjid; Any Niatun (UNIB Press, 2023)
This research is Classroom Action Research (CAR). The aim of the research is to improve Mathematics learning outcomes regarding Addition of Two Numbers using Saving Techniques for grade II students at SD Negeri 2 Merauke for the 2022/2023 academic year by using the Addition Board (Pajum) teaching aid until they reach the Minimum Completeness Criteria (MCC). The research is said to be successful if all students have reached the MCC 65. The results of the research show that there has been an increase, that Pajum teaching aids make learning material more interesting and simple. So it shows that there was an increase in the percentage of learning outcomes in Mathematics subjects before the action of 12 (43%) students who completed the first cycle, there was an increase to 18 (64%) students and after the second cycle it increased to 28 (100%) students who completed it. In accordance with the aim of this research, namely the use of Pajum teaching aids can improve learning outcomes about Adding Two Numbers with Saving Techniques for grade II SD Negeri 2 Merauke for the 2022/2023 Academic Year until they reach the MCC.